Improvement in cowpea variety Videza for traits of extra earliness and higher seed yield. Issue 12 (December 2022) - Dorvlo, Innocent Kwaku; Amenorpe, Godwin; Amoatey, Harry Mensah; Amiteye, Samuel; Kutufam, Jacob Teye; Afutu, Emmanuel; Asare-Bediako, Elvis; Darkwa, Alfred Anthony
Abstract: The cowpea variety Videza, which was used as the control, matures early (70 days after planting), although it produces low yields. Gamma irradiation mutagenesis was used to induce Videza into extra-early maturing and higher yielding mutant genotypes. A single seed descend population was developed for radio-sensitivity test, and a Lethal Dose 50 (LD50 ) of 240.5 Gy was determined, and applied from a cobalt-60 ( 60 Co) source, to acutely mass irradiate 1800 Videza seeds, at the Ghana Atomic Energy Commission. The irradiated seeds (M1) were planted to produce M2 seeds bearing plants and subsequently advanced to M3 plants for selection of nine induced plants based on extra earliness and significantly higher seed yields than the parental control. It took 48 days after planting (DAP) for the genotype coded P1N02#1 to reach 50 % maturity followed by 52 DAP for genotypes with codes P4N03#3; P3N01#5; P5N05#6, P4N14#7, P5N07#8, P5N05#10 and 54 DAP for genotype P4N14#11. P1N06#9 had the highest yield (97.38 g/plant), followed by P5N05#10 (95.97 g/plant), P1N08#13 (81.24 g/plant), P2N09#12 (73.94 g/plant), P6N10#19 (70.83 g/plant), P1N06#20 (65.36 kg/plant), P5N07#14 (61.23 g/plant), P4N14# (58.05 g/plant) and P1N08#17 (56.23 g/plant). M3 seeds were advanced to M4 plants for a Preliminary Yield Trial which revealed that induced plants P5N05#10 (1235 kg/ha), P2N09#12 (1206 kg/ha), P5N07#14 (1185 kg/ha), P1N06#20 (1171 kg/ha), P1N06#9 (1051 kg/ha), P1N08#13 (1041 kg/ha), and P6N10#19 (999 kg/ha) outperformed the control (517 kg/ha) and two other commercial varieties. Overall, the two highest performing candidates for further evaluation for varietal release were P5N05#10 and P2N09#12. Abstract : Mutagenesis; Development, Extra early; Radiosensitivity, Cowpea; Agriculture.